EVALUATION OF THE USE OF SMART GLASSES IN IRS LOGISTICS - Tomas BINAR; Simona VASIKOVA; Pavel SAFL (Scientific Journal of Silesian University of Technology. Series Transport, 2022)
To effectively transport materials through different means of transport, it is essential to have an optimized warehouse logistics first. Thanks to the Industry 4.0 platform, there are several ways to accomplish the delivery of materials from a warehouse through transport by road, rail or air. This paper deals with a primary warehouse problem, which is the fast and accurate search and selection of required items in the stock. For this issue, the use of smart glass technology and its implementation in the logistic processes of warehouses could help. In a particular way, an IRS (Integrated Rescue System) warehouse was selected as an example. The augmented reality (AR) type of glasses was selected. The introductory part of this paper deals with the current situation in the warehouse and logistic processes, where the problem of lack of qualified staff and material supply is prevalent, particularly during different crisis situations, such as pandemics or high employee turnovers. The use of smart glasses is one of the many possible problem-solving variants in this field. Further, a basic description of smart glasses, possible uses and sorting are presented in this paper. For the experiment, it was necessary to choose several different commercially available models of smart glasses. An evaluation was provided by the Simple comparative method, Saaty's method and Linear partial utility function method and the best options were identified. Also, there is an example of smart glasses application for picking a particular component in an IRS warehouse in the last part of this paper.